Effect of endophytic bacterium Curtobacterium citreum PLPL and chitosan on plant growth enhancement and management of potato black scurf and stem canker (Annals of Bangladesh Agriculture, 2025)
Rhizoctonia stem canker and black scurf of potato are the most prevalent and widespread soil-borne fungal diseases that cause notable reduction in the yield of potato globally. The purpose of the current study was to assess the effect of both Curtobacterium citreum and chitosan, either alone or in combination, on the prevention of potato Rhizoctonia diseases and its growth-promoting characteristics. The antagonistic capability of the endophytic bacteria C. citreum PLPL and chitosan against R. solani was evaluated and got potential responses. Following that, compatibility tests between C. citreum and chitosan were conducted, revealing compatibility between the natural agents. Prior to sowing, seed tubers were treated with C. citreum (108 colony forming units per mililiter) and chitosan at 1.0 % concentration. In comparison to pathogen-inoculated plots, all individual and combined treatments increased growth and yield while reducing disease incidence and severity. The combination of C. citreum and chitosan resulted in the significant reduction in disease incidence (79.95% for stem canker and 65.53% for black scurf) and percent disease index (85.14% for stem canker and 66.00% for black scurf) over the pathogen-inoculated plot. The combination of C. citreum with chitosan resulted in a maximum yield of 43.15 t/ha, with all growth parameters significantly increased. In addition to increasing potato yield, treating tubers with a combination of C. citreum and chitosan may be a sustainable and environment friendly method of managing stem canker and black scurf diseases. Ann. Bangladesh Agric. 28(2): 71-87